2014
DOI: 10.1007/s11104-014-2091-z
|View full text |Cite
|
Sign up to set email alerts
|

The return of an experimentally N-saturated boreal forest to an N-limited state: observations on the soil microbial community structure, biotic N retention capacity and gross N mineralisation

Abstract: Background and aims To find out how N-saturated forests can return to an N-limited state, we examined the recovery of biotic N sinks under decreasing N supply. Methods . We studied a 40-year-old experiment in Pinus sylvestris forest, with control plots, N0, three N treatments, N1-N3, of which N3 was stopped after 20 years, allowing observation of recovery. Results In N3, the N concentration in foliage was still slightly elevated, but the N uptake capacity of ectomycorrhizal (ECM) roots in N3 was no longer lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 76 publications
(102 reference statements)
2
17
1
Order By: Relevance
“…ECM fungal richness, diversity, and evenness were not significantly different across N fertilization treatments. These results reconcile with earlier studies in oak [30] and spruce forests [3,[47][48][49], but seemingly contradict the majority of studies that show a rapid and substantial decline in ECM fungal diversity following N fertilization [e.g., 6,[9][10][11]30] and increasing soil N levels along natural gradients of productivity [50]. This result may reflect the short period (three years) over which the plots were fertilized [6,51] or (more likely) that high levels of ambient N deposition may have pre-empted any effects of the experimental N additions.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…ECM fungal richness, diversity, and evenness were not significantly different across N fertilization treatments. These results reconcile with earlier studies in oak [30] and spruce forests [3,[47][48][49], but seemingly contradict the majority of studies that show a rapid and substantial decline in ECM fungal diversity following N fertilization [e.g., 6,[9][10][11]30] and increasing soil N levels along natural gradients of productivity [50]. This result may reflect the short period (three years) over which the plots were fertilized [6,51] or (more likely) that high levels of ambient N deposition may have pre-empted any effects of the experimental N additions.…”
Section: Discussionsupporting
confidence: 75%
“…As a result, mycorrhizal diversity may underpin many forest ecosystem services including nutrient cycling and water use efficiency. Although studies have widely demonstrated declines in ECM diversity and changes in ECM community composition following N-enrichment [3,[6][7][8][9][10][11][12], the extent to which these changes influence the functional capacity of ECM is less well understood [13][14][15][16]. In this study, we examined the diversity and functioning in ECM communities under ambient N deposition and following N fertilization in an urban-adjacent Pinus elliottii plantation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to global warming and increased levels of CO 2 , however, their effects are largely local. Since N is a limiting nutrient in most terrestrial ecosystems, including boreal and temperate forests (255), anthropogenic N deposition may strongly influence NPP in these environments by reducing this limitation (256). N deposition also has a range of additional consequences that range from shifts in the soil C/N ratio, soil acidification, and root exudation to changes in the vegetation and microbiota (257).…”
Section: Nitrogen Depositionmentioning
confidence: 99%
“…There appears to be a general consensus that N deposition increases soil C sequestration due to the decline in SOM decomposition via the reduction of biomass and activity of soil microbial populations in many different soil environments, including temperate and boreal forests (258,(260)(261)(262)(263)(264). The most probable reason for C sequestration is the observed reduction of tree root exudation (256), although direct effects of a pH decrease induced by N deposition were proposed as an alternative explanation (265). Although the reduction of biomass following N input was mostly observed in fungi (256,266), it was recently noted that the biomass of soil bacteria can be reduced as well, by up to 50% (258,263,267).…”
Section: Nitrogen Depositionmentioning
confidence: 99%
See 1 more Smart Citation